The Interpretation of “diaspora” in Chinese Language: its Diversity and Influence on Social Theory and Practice - N. Van; E. O. Leonteva (Дискурс, 2023)
Introduction. The Chinese language, unlike Russian, has several terms,  denoting different statuses of Chinese migrants, but there  is no term  such as “diaspora”. These  features  are interpreted  by the  authors  along the  lines of social ontology as independent  sociological concepts, constructing  particular migrant groups. The article’s oobjective  is to show their internal coherence and correlation  with the notion  of “diaspora” as well as to outline the difficulties and problems  occurring  as  the  result  of the  interaction  between  researchers dealing with the topic. The relevance of the study stems  from the fact that researchers have paid little attention  to differences in national academic  discourses  that are meanwhile very important because intercultural differences can only be negotiated  if there  is an understanding  of what they are.  With regard  to diaspora  discussions,  this understanding has  yet to be  developed.  The article  shows  that  in diaspora  studies  there  is a language barrier,  which at the  moment  is currently an impassable obstacle for authors  who write about the diaspora in different languages.Methodology and sources. To work on the article, the authors  used a discursive analysis of academic  texts  on Chinese migration and Chinese migrants, as well as dictionaries  and official documents  such as the Large Chinese-Russian Dictionary, the Tsihai Dictionary (辞海 ci hai – Sea of words), the Large Russian Encyclopedia, State Council resolutions, and Chinese legislation.Results and  discussion. The treatment of 10 terms  replacing the notion of “diaspora” in Chinese language is disclosed. The authors  describe  characteristic features  of each group. It is illustrated that there is a linguistic asymmetry, as a result of which the European notion of  “diaspora”  receives  specific  connotations  when  translated   into  Chinese  that  cannot account  all the  features  of this community,  thus  in the  Chinese  academic  discourse  the substitution   with  the  most  important   from  the  translator   and  editor's   point  of  view equivalent (the situation “instead of diaspora”) is made.Conclusion.  It  is concluded  that  in Chinese,  through  translation,  the  author  expresses important  features of  the  migrant  community,  emphasising  either  its  closeness, or  its distance to the “diaspora” status.